Hypertriglyceridemia-induced pancreatitis in pregnancy and its management issues: A case-based study - Babul Reddy Hanmayyagari; Jyoti Wadwa; Mounika Guntaka; Balamurali Krishna (Apollo Medicine, 2020)
Hyperlipidemia in pregnancy has grave complications; lipid levels in pregnancy are influenced by genetic and hormonal factors, primarily due to estrogen. Here, we present a case of acute pancreatitis with hypertriglyceridemia presenting during the second trimester of pregnancy. We also discuss the management issues of this entity during pregnancy.